The Jesuit mission to New France : a new interpretation in the light of the earlier Jesuit experience in Japan - Abé, Takao (Studies in the history of Christian traditions, 2011)
A new interpretation of the Jesuit mission to New France is here proposed by using, for comparison and contrast, the earlier Jesuit experience in Japan. In order to present revisionist perspectives of the Jesuit missions based on a broader international framework beyond North America, the existing historical paradigms of the Jesuit missionary activity to Amerindians based on the limited regional history of New France are re-examined.